THE IMPLEMENTATION OF THE EXPERIMENTAL METHOD AND ITS EFFECT ON IPAS LEARNING ACHIEVEMENT AMONG FOURTH-GRADE STUDENTS AT MI MA’ARIF GONDANG, WATUMALANG, WONOSOBO - Zumrotus Sholehah; Muhtar Sofwan Hidayat; Sri Jumini (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2026)
Improving student learning outcomes and engagement in science remains a challenge in Indonesian elementary schools, highlighting the need for effective teaching methods. This study aims to determine the effect of the application of the experimental method on student learning achievement in the subject of science for grade IV at MI Ma'arif Gondang Watumalang Wonosobo, as well as to analyze the improvement in learning outcomes and student responses to learning. This study uses a quantitative approach with a quasi-experimental design of the non-equivalent control group design. The subjects of the study consisted of two classes, namely the experimental class and the control class with a total of 32 students each. Data collection techniques include tests (pretest and posttest) and student response questionnaires. The results of the study showed that there was a significant increase in student learning achievement in the experimental class after the application of the experimental method. The average pretest score of the experimental class was 45.81, increasing to 82.47 in the posttest, while the control class increased from 39.81 to 67.90. The results of the hypothesis test showed a significance value of 0.000 <0.05, which means there is a significant effect of the experimental method on student learning achievement. In addition, the results of the N-Gain analysis showed that the increase in learning outcomes in the experimental class was in the medium to high category (68.77), higher than the control class (50.61). Student responses to experimental learning also showed positive results, where students were more active, enthusiastic, and easily understood the material.